Mycelium-wood composites as a circular material for building insulation - Candido, Alessia; Amiri, Ali; Junnila, Seppo; Pittau, Francesco (Frontiers in Sustainable Cities, 2024)
In Europe, buildings account for 40% of the energy consumption and produce 36% of CO2 emissions. Renovation could be a great tool to decarbonize the building stock since it allows for a decrease in the operational energy required for buildings and is less material-consuming than new construction. Further benefits are brought by the usage of bio-based insulation materials that can drastically reduce embodied emissions and transform structures into factual carbon sinks. This study focuses on a particular kind of biogenic material, mycelium-wood composites, consisting of organic matter bound by the root structure of fungal organisms. This innovative insulation material was compared with traditional ones for the renovation of the building stock, with a focus on vertical components like walls in the Helsinki metropolitan area. To characterize mycelium-wood composites, density and carbon content information were gathered from the samples realized in the Politecnico di Milano MaBa.SAPERLab, while the production processes were included in a SimaPro model to obtain the GWP value. Different scenarios were then defined by two variables: the renovation rate of the building stock and the market penetration of mycelium-wood composites. For each scenario, the overall GWP and CO2 stored values were calculated. Results show the great potential of the innovative material that grants carbon storage in the building stock that could even surpass the amount stored in the 32,500 ha of forest in the area. However, this possibility is heavily influenced by factors independent of the type of insulation used that should be further investigated.